(untitled) (CAHIERS MAGELLANES-NS, 2024)
Cognitive biases such as overconfidence, anchoring, and confirmation bias are pervasive in managerial decision-making, often leading to suboptimal outcomes and impaired organisational performance. This paper theorises the impact of these cognitive biases from a neuroeconomic perspective and proposes interventions to mitigate their effects. By reviewing existing literature, we explore the neural underpinnings of these biases, identifying key brain regions and neural processes involved. We then propose a set of neuroeconomic interventions, including neurofeedback, cognitive training, and mindfulness practices, which target these neural mechanisms to reduce bias. Neurofeedback aims to enhance managers' awareness and control over their neural activity, improving decision accuracy. Cognitive training focuses on strengthening executive functions, enabling managers to process information more effectively and avoid anchoring. Mindfulness practices promote emotional regulation and cognitive flexibility, helping managers counteract confirmation bias and remain open to new information. The potential impact of these interventions on decision quality and organisational performance is discussed, emphasising how they can lead to more accurate risk assessments, better strategic decisions, and enhanced overall performance. This paper contributes to the field of neuroeconomics by integrating cognitive neuroscience and management theory, offering a comprehensive framework for understanding and addressing cognitive biases in managerial contexts.